Open-Label, Single-Arm, Multicenter, Phase II Trial of Lenvatinib for the Treatment of Patients With Anaplastic Thyroid Cancer. Issue 21 (20th July 2021) - Wirth, Lori J.; Brose, Marcia S.; Sherman, Eric J.; Licitra, Lisa; Schlumberger, Martin; Sherman, Steven I.; Bible, Keith C.; Robinson, Bruce; Rodien, Patrice; Godbert, Yann; De La Fouchardiere, Christelle; Newbold, Kate; et al.
Abstract : PURPOSE: Anaplastic thyroid cancer (ATC), an aggressive malignancy, is associated with a poor prognosis and an unmet need for effective treatment, especially for patients without BRAF mutations or NTRK or RET fusions. Lenvatinib is US Food and Drug Administration–approved for radioiodine-refractory differentiated thyroid cancer and has previously demonstrated activity in a small study of patients with ATC (n = 17). We aimed to further evaluate lenvatinib in ATC. METHODS: This open-label, multicenter, international, phase II study enrolled patients with ATC, who had ≥ 1 measurable target lesion, to receive lenvatinib 24 mg once daily. The primary end points were objective response rate (ORR) by investigator assessment per RECIST v1.1 and safety. Responses were confirmed ≥ 4 weeks after the initial response. Additional end points included progression-free survival and overall survival (OS). RESULTS: The study was halted for futility as the minimum ORR threshold of 15% was not met upon interim analysis. The interim analysis set included the first 20 patients. The full analysis set includes all 34 enrolled and treated patients. In the full analysis set, one patient achieved a partial response (ORR, 2.9%; 95% CI, 0.1 to 15.3). More than half of the evaluable patients experienced tumor shrinkage; three patients experienced a > 30% tumor reduction. The median progression-free survival was 2.6 months (95% CI, 1.4 to 2.8); the median overall survival was 3.2 months (95% CI, 2.8 to 8.2). The most common treatment-related adverse events (AEs) were hypertension (56%), decreased appetite (29%), fatigue (29%), and stomatitis (29%). No major treatment-related bleeding events or grade 5 treatment-related AEs occurred. CONCLUSION: The safety profile of lenvatinib in ATC was manageable, and many AEs were attributable to the progression of ATC. The results suggest that lenvatinib monotherapy may not be an effective treatment for ATC; further investigation may be warranted.